»Ke slovu je potřeba se doposlouchat«. Audio art a tekstowo-dźwiękowa twórczość Jaromíra Typlta - Pospiszil, Karolina (Komisja Slawistyczna PAN, Oddział w Poznaniu, IFS UAM, Wydawnictwo PRO, 2013)
In the following article I present text-sound works of Jaromír Typlt on the background of one of the most interesting phenomena in contemporary Czech culture, which is audio art. Reflection on audio art and sound poetry is an introduction to writer’s works. His textes and compositions from borderland of arts, especially so-called zmutovaná autorská čtení and a cycle Audio, which raises issue of sound, hearing and their connections with literature also are analyzed in this article.
Keywords: Audio art; Jaromír Typlt; Czech poetry; literature; sound; sound poetry